Analysis of Strengths, Weaknesses, Opportunities, and Threats of Technological Pedagogical Content Knowledge of Sociology Teachers in Boyolali Regency - Rohmah, Nur Rohmah Nur; Liestyasari, Siany Indria Liestyasari Siany (Journal of English Language and Education, 2026)
Twenty-first century education emphasizes the integration of technology as a key requirement in the implementation of Sociology learning. The relevant framework for responding to this requirement is Technological Pedagogical Content Knowledge (TPACK). This study aims to analyze the implementation of TPACK in Sociology learning in Boyolali Regency Senior High Schools using the SWOT analysis approach. The research data were analyzed based on the aspects of strengths, weaknesses, opportunities, and threats to find the right strategy using the SWOT matrix. The results of the analysis show that teachers' fairly good understanding of TPACK with a variety of technology uses and school facility support are the main strengths. However, limitations in teachers' technological competence, limitations in the devices used, and dependence on the internet network are still obstacles. Government support and teachers' freedom to innovate are opportunities that can be utilized to support the optimization of Sociology learning with the TPACK framework. Meanwhile, misuse of technology, student distractions, and dynamic education policies are threats that need to be addressed. These findings indicate that the implementation of TPACK in the Sociology learning process still requires strengthening teachers' competencies and sustainable policies so that Sociology learning can run effectively.